Biomass–density data analysis: a comment on Cabaço et al. (2013). (27th January 2015) - Vieira, Vasco M. N. C. S.; Leitão, Francisco; Mateus, Marcos; Austin, Amy
Summary Appropriate use of mathematics and statistics is fundamental for sound interpretations of ecological results and to prevent inaccurate conclusions. Throughout the article by Cabaço et al. (2013) emerge cases of biased data analyses including absence of statistical tests, application of unsuited tests, inconsistent geometrical interpretation of xy data scatter, among others. These biases congregated into incorrect conclusions including (i) reporting a generalized nutrient limitation of seagrass meadows, (ii) proposing the intraspecific biomass–density relation of seaweeds as an ecological indicator, when results report little more than randomness, thus suggesting this relation is unsuited as an ecological indicator; (iii) contradicting general ecological theory without any statistical evidence; and (iv) misassociating their results to the ones by other authors. Synthesis. In order to help ecological researchers pinpoint sources of bias, we point out mistakes related to xy data analysis in Cabaço et al. (2013) that can occur in any subject area and flag others specific to biomass‐density relations.